The Use of an Accounting Information System, Action and Organizational Performance. - Lucas, Henry C. (The Accounting Review, 1975)
The article examines the use of an accounting information system for evaluating the success of an organization. A descriptive model of the relationship among classes of variables affecting performance, the use of information, and action is described by the author. Performance is expected to be influenced by a number of variables which are likely to have a low correlation with performance. Performance is expected to be influenced by a number of situational and personal factors based on the results of several past studies of sales force performance. The organization involved in this article is a major California bank with more than 200 branches in the state. Branch banking in California is unique; there is fierce competition even for retail business which is usually ignored by commercial banks in other states. The bank is a major user of computers and has a number of information systems producing reports for distribution to branch management. Interviews were held with members of the information systems department staff to select reports which have managerial significance, that is, which provide information beyond routine operational data.